New Techniques for Disconnector Switching VFT Mitigation in GIS - Abdelrahman Said Abdelrahman; Mousa Awad Allah Abd-Allah; Ebrahim A Badran (Institute of Advanced Engineering and Science, 2014)
Switching operations in a Gas Insulated Substations (GIS) generate very fast transient over voltages (VFTO) which are dangerous for the transformer and the system insulation because of their short rise time. Under special circumstances the overvoltages can arise close to the transformer Basic Insulation Level (BIL). The reduction of VFTO amplitudes is considered main challenges. Therefore, VFTO in the 220 kV Wadi-Hoff GIS is analyzed and the worst case for disconnector switching is predicted using EMTP/ATP in this paper. VFTO mitigation techniques are studied in this work. Furthermore, proposed techniques are presented for mitigating the VFTO. The proposed techniques can be used by the maintenance engineers, transformer designers, and GIS insulation manufactures. The results show that the proposed techniques highly reduce the VFTO in a simple manner.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5186